The effect of cold ambient temperatures on climbing-specific finger flexor performance. Issue 7 (9th August 2017) - Phillips, Kevin; Noh, Byungjoo; Gage, Matthew; Yoon, Tejin
Abstract: Different ambient temperatures are known to affect muscular performance based on the type of contraction. The effect of cold (10°C) and thermoneutral (TN) (24°C) ambient temperatures on finger flexor performance was examined in 12 rock climbers. After 30 min of seated rest in the designated temperature condition, participants completed maximal voluntary contractions (MVC) on a climbing-specific finger flexor assessment device equipped with a crimp grip hold. Participants then completed an intermittent fatiguing task until failure. The fatiguing task consisted of 10-s contractions at 40% MVC followed by a 3-s of rest. MVC recovery was assessed immediately, 5, 10, and 15 min post-task failure. Estimated muscle temperature and subjective thermal ratings were significantly lower throughout testing in the cold condition ( P  < .001). Finger flexor MVC strength was similar between conditions at baseline and throughout recovery. Time to task failure was significantly longer (364 ± 135 vs. 251 ± 97 s, P  = .003) and force time integral was greater (53, 715 ± 19, 988 vs. 40, 243 ± 15, 360 Ns, P  = .001) during the cold condition. No significant differences were found between conditions for force variability or electromyography (EMG) at the start and end of the fatiguing task. However, the rate of increase in EMG for the TN condition was significantly faster ( P  = .03). These results suggest important implications for researchers when examining climbing performance, especially in outdoor settings where temperatures may vary from day to day. Inconsistencies in testing temperatures might significantly affect muscular endurance.